Unveiling the potential of linseed mucilage, its health benefits, and applications in food packaging - Chand, Monika; Chopra, Rajni; Talwar, Binanshu; Homroy, Snigdha; Singh, Priyanka Kumari; Dhiman, Aishwarya; Payyunni, Abdul Wahid (Frontiers in Nutrition, 2024)
Industrial waste products derived from the oil industry, often contain valuable substances and elements with great potential. These by-products can be used for various purposes, including as nutrients, bioactive compounds, fuels, and polymers. Linseed mucilage (LM) is one of such example of a beneficial byproduct obtained from linseed. It possesses favorable chemical and functional properties depending on its method of extraction. Different pretreatments such as enzymatic, microwaves, pulse electric field, and ultrasound have been explored by various researchers to enhance both yield and quality of mucilage. Furthermore, LM has exhibited therapeutic effects in the treatment of obesity, diabetes, constipation, hyperlipidemia, cancer, and other lifestyle diseases. Additionally, it demonstrates favorable functional characteristics that make it suitable to be used in bioplastic production. These properties preserve food quality, prolong shelf life, and confer antimicrobial activity. It also has potential to be used as a packaging material, especially considering the increasing demand for sustainable and biodegradable alternatives to plastics because of its detrimental impact on the environmental health. This review primarily focuses on different extraction techniques used for linseed mucilage, its mechanism of action in health benefits, and potential applications in food packaging.